2014
DOI: 10.5216/ree.v16i2.20782
|View full text |Cite
|
Sign up to set email alerts
|

Perfil sociodemográfico, econômico e de saúde de idosos rurais segundo o indicativo de depressão

Abstract: Perfil sociodemográfico, econômico e de saúde de idosos rurais segundo o indicativo de depressão* Sociodemographic, economic and health profile of the rural elderly, according to depression indicatorsPerfil sociodemográfico, económico y de salud de ancianos rurales según el indicativo de depresión

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
15

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 15 publications
0
4
0
15
Order By: Relevance
“…In RA, the lowest score found was in sensory abilities, a facet that analyzes sensory capacity and the impact of the loss of sensory abilities. Despite improved access to health services, the elderly require a wide network of care, something which has not yet been satisfactorily established in RA, and the absence of which can lead to greater impairment in this aspect, due to the lack of, for example, specialized care 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In RA, the lowest score found was in sensory abilities, a facet that analyzes sensory capacity and the impact of the loss of sensory abilities. Despite improved access to health services, the elderly require a wide network of care, something which has not yet been satisfactorily established in RA, and the absence of which can lead to greater impairment in this aspect, due to the lack of, for example, specialized care 29 .…”
Section: Discussionmentioning
confidence: 99%
“…A study on access to and the use of health services by rural elderly people, based on IBGE data, concluded that in UA there is greater ease of access to health services and higher incomes, which facilitates a positive view of quality of life 31 . Another related factor refers to income, which is generally higher in urban environments, allowing the acquisition of consumer goods and the practice of sports and leisure activities, positively affecting QoL 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The process of urbanization Brazil 2 acts directly on such social contexts, and gives population aging among the urban and rural elderly peculiar, differentiated characteristics, even though both groups were born and lived in the same time period. These differences include economic development, employment opportunities, cultural diversity and the availability and access to goods and services in urban and rural areas, as the greatest public investments in health are concentrated in urban scenarios 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a greater stability in personal relations has been perceived in rural environments, allowing greater solidification of the affective ties between the population 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Instrumento esses do qual mais se destaca como escala de depressão geriátrica e inventário de depressão de Beck. (LEAL et al, 2014;RODRIGUES et al, 2014;GOMES;OLIVEIRA, 2013) No entanto inventario de depressão de Beck não pode ser utilizado por enfermeiros e sim por psicólogos por se tratar de um instrumento diagnóstico da área de psicologia. Embora seja um instrumento bastante utilizado em pesquisas de enfermeiros teoricamente ele não deveria ser utilizado pelos mesmos (PARANHOS; ARGIMON;WERLANG, 2010;GANDIN et al, 2007) Outro fator relevante a este instrumento é que é necessário comprar a escala de uma editora nacional de psicologia: A casa do psicólogo.…”
Section: Metodologiaunclassified